2004
DOI: 10.1160/th03-11-0722
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy of ultrasound in the diagnosis of deep venous thrombosis in asymptomatic patients

Abstract: Evaluation of the accuracy of ultrasound has yielded heterogeneous results. Our objective was to summarize the evidence on the accuracy of ultrasound compared to venography in asymptomatic patients, taking into account the variation due to threshold differences. Searches of journal table of contents, computer databases (Medline, Embase, Biomed, Cochrane) and conference proceedings were performed. A study was eligible if it prospectively compared ultrasound to venography for the diagnosis of DVT in asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 76 publications
(81 reference statements)
2
28
0
Order By: Relevance
“…Our study, however, focused on asymptomatic DVT patients and symptomatic DVT occurred in just three patients of the 32 patients, compared with asymptomatic DVT in seven of 32 patients. Symptomatic DVT patients have been known to be objectively far less common than in screening tests including asymptomatic DVT patients (Kassaï et al, 2004). Girard et al (1999) reported that 82% of patients with acute PTE still displayed detectable residual DVT at the time of PTE diagnosis, and DVT remains asymptomatic in nearly two-thirds of PTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, however, focused on asymptomatic DVT patients and symptomatic DVT occurred in just three patients of the 32 patients, compared with asymptomatic DVT in seven of 32 patients. Symptomatic DVT patients have been known to be objectively far less common than in screening tests including asymptomatic DVT patients (Kassaï et al, 2004). Girard et al (1999) reported that 82% of patients with acute PTE still displayed detectable residual DVT at the time of PTE diagnosis, and DVT remains asymptomatic in nearly two-thirds of PTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 45 studies, 42 were published in English, 2 in French [35,36], and 1 in Italian [37]. Detailed results of this meta-analysis are published elsewhere [38]. One article was missed when only the Medline database was searched, and one level 1 and three level 2 studies were missed when the Medline search was limited to English-language articles.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the difficulty inherent in the evaluation of diagnostic tests and lack of reliable studies make any adjustment impossible. Systematic review of diagnostic tests could gainfully be used to evaluate the quality and summarize the accuracy of potentially unbiased studies with appropriate meta-analytic methods [65]. Unfortunately, as shown by recent metaanalyses, most studies are potentially biased or do not report in sufficient detail patient or study features that might influence diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 99%